KEWAJIBAN IMUNISASI DASAR, MANFAAT DAN KEAMANAN - Fadhli Rizal Makarim (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2017)
Immunizations became serious world issues. A shared awareness to improve the nation’s health is not only a priority for developed countries but has become a common concern for most countries. WHO linked this adaptation campaign with the Sustainable Development Goals (SDGs) to be achieved by 2030. Completed basic immunization data based on routine data in 2010-2013 has reached the target of the Ministry of Health's Strategic Plan, but in 2014 and 2015 it did not achieve the desired target. In 2015, coverage of basic immunization in infants in Indonesia reaches 86.5% compared to the target of a strategic plan that should reach 91%. In 2016, the basic immunization coverage finished up to 91.1%. The achievement of coverage basic immunization in Semarang has reached the minimum target that as 95% compared to the target in 2015. Operational strategy is quite high and evenly can be seen from the completeness of Universal Child Immunization (UCI) of the district. In 2016, the number of districts that have reached UCI with coverage criteria DPT 3, polio, and measles> 80%, as many as 177 urban districts from 177 urban district in Semarang (100%). The assessment of the safety and effectiveness of basic immunization in infants and children is still a social problem. The issue of vaccine rejection must be managed carefully. There is strong evidence supporting the MMR vaccine is not associated with the incidence of autism in children. Other strong evidence also suggests that MMR, DPT, Hib, and Hepatitis B vaccines are not associated with leukaemia in children. Evidence of serious post-immunization events is extremely rare and has a very low absolute risk.